Permafrost and active layer characteristics in the high arid Andes between the Altiplano and high Atacama Desert - Yoshikawa, Kenji (2025)
The thermal and hydrological regime of permafrost in the arid Andes is unique due to the combination of extreme aridity, high solar radiation, and significant diurnal temperature fluctuations. Drilling at Chachani (6,057 m.a.s.l.), Aucanquilcha (6,176 m.a.s.l.), Chajnantor (5,640 m.a.s.l.), and Ojos del Salado (6,893 m.a.s.l.) volcanoes revealed both dry permafrost and ice-rich permafrost in one of the driest areas on Earth. We monitored solar radiations and ground temperature conditions at twenty-four sites on eleven mountains between 1° and 33° S. At elevations above 5,800 m, the active layer is about 10 to 30 cm thick and is controlled by diurnal fluctuations. Near the lower limit of mountain permafrost (LLMP), the thermal offset is positive and ice-rich terrains are found that are associated with moisture percolating from penitentes. Above 6,400 m, the surface energy balance is dominated by sublimation and dry permafrost was found. Near LLMP elevation, snow ablation was dominated by melting during summer, and ice-rich permafrost was present. We found that the type of snow ablation varies with elevation and affects the thermal properties of the permafrost in the arid Andes.